A threshold flux phenomenon for colloidal fouling in reverse osmosis characterized by transmembrane pressure and electrical impedance spectroscopy - Ho, Jia Shin (2016)
The dependence of membrane fouling on flux has been investigated using silica as the model foulant in a crossflow membrane module operated at constant flux. Electrical impedance spectroscopy (EIS) was used to monitor the electrical properties of the fouling process. We show that the nature of a flowing colloidal suspension of silica on the membrane surface changes when a transition or threshold flux is reached. This transition was well-defined and was reflected in the changes of the slope of transmembrane pressure (TMP) with flux and the conductance of the diffusion polarization (DP) layer determined by EIS. The threshold flux increased with increasing crossflow velocity. The effect of a spacer in the feed channel was also investigated and the presence of spacer increased the threshold flux. The conductance of the diffusion polarization layer (GDP) derived from the low frequency region in the EIS was identified as the most important EIS parameter for signaling the onset of cake formation and the cake enhanced concentration polarization (CECP) effect. TMP measurements on their own provided limited information on these phenomena. The threshold flux was affected strongly by the crossflow velocity and this was also illustrated in the change in the minimum of the GDP with increasing flux. This study suggests that EIS could be applied "online" using a side-stream, 'canary' cell to continuously monitor a reverse osmosis system to ensure its operations remain below the threshold flux. Keywords: Cake enhanced concentration polarization (CECP); Diffusion polarization; Electrical impedance spectroscopy; Threshold flux; Transmembrane pressure